Morphodynamics of fetch-limited beaches in contrasting environments - Freire, Paula (2017)
Sandy beaches can be found in fetch-limited environments that are protected from ocean generated waves, as estuaries, lagoons, and backbarriers, and where fetch characteristics allow local wind-generated waves to develop and maintain a beach. The morphodynamics of these low-energy beaches present a peculiar behaviour and general open-ocean models are inappropriate for their study.